Synthesis of 3-Substituted-5-(4-carboxycyclohexylmethyl)-tetrahydro-2H-1,3,5-thiadiazine-2-thione Derivatives as Antifibrinolytic and Antimicrobial Agents - Özçelik, Azime Berna; Ersan, Seyhan; Ural, Ali Uğur; Özkan, Semiha; Ertan, Mevlüt (Arzneimittelforschung, 2007)
A series of 3-substituted-5-(4-carboxycy-clohexylmethyl)-tetrahydro-2H-1,3,5-thiadiazine-2-thione derivatives was prepared and examined for antifibrinolytic and antimicrobial activities. Their structures were elucidated by spectral methods. Antifibrinolytic activities of these compounds, were investigated in vitro and compared to tranexamic acid (CAS 1197-18-8). Among the synthesized compounds, 3-methyl-5-(4-carboxycyclohex-ylmethyl)-tetrahydro-2H-1,3,5-thiadia-zine-2-thione (Ia) was the most prominent one (104 %) when compared to tranexamic acid. Besides, 3-ethyl-5-(4-carboxycyclohexyl-methyl)-tetrahydro-2H-1,3,5-thiadiazine-2-thione (Ib), 3-iso-propyl-5-(4-carboxycyclohexylmethyl)-tetrahydro-2H-1,3,5-thiadiazine-2-thione (Id) and 3-isobutyl-5-(4-carboxycyclohex-yl-methyl)-tetrahydro-2H-1,3,5-thiadia-zine-2-thione (Ig) showed antifibrinolytic activity similar to tranexamic acid. Antibacterial activities of these compounds against Gram-positive bacteria (Staphylo-coccus aureus, Bacillus subtilis), Gram-negative bacteria (Escherichia coli, Pseu-domonas aeruginosa) and yeast-like fungi (Candida albicans, Candida tropicalis) were investigated by the micro-dilution method and compared with the activity of tranexamic acid, ofloxacin and flucon-azole. By this way their minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and minimal fungicidal concentration (MFC) values were determined. Compound Ia exhibited almost equally potent activity against B. subtilis (MIC and MBC: 6.25 μg/mL). Compounds Ib-Id, If-Ig and In exhibited similar bactericidal activity against B. subtilis (MBC: 12.5 μg/mL). Compounds Ik and Im showed bacteriostatic activity against S. aureus. None of the compounds exhibited activity against Gram-negative bacteria. On the other hand, all compounds had potent antifungal activities against the yeast utilized. Among the synthesized compounds, 3-methyl-5-(4-car-boxycyclohexylmethyl)-tetrahydro-2H-1,3,5-thiadiazine-2-thione (Ia) seems to be the most effective compound with antifibrinolytic and antimicrobial activity.
Keywords: Antifbrinolytic agents; Antimicrobial agents; Tetrahydro-2H-1,3,5-thiadia-zine-2-thione derivatives; Tranexamic acid